The Arctic regions : compiled from the latest information 1925 / published by the U.S. Navy Hydrographic Office - United States. Hydrographic Office (Washington, D.C. : Hydrographic Office, 1926)
3d July 1926 Relief shown by spot heights. Depths shown by soundings.; Annotated to show British Admiralty, Danish, Russian and Hydrographic Office nautical chart sheet coverage.; Chart no. 2560 Grayscale; 1:6,760,000